Evaluating the efficacy of HRZE-based regimens in a high-burden murine model: a back-translational assessment of rifamycins and moxifloxacin substitutions in tuberculosis treatment - Cummings, Jason E.; Woolhiser, Lisa K.; Guglielmi, Vincent; Wernsman, Machenzie; Romano, Ashley; Pauly, Samantha; Belisle, John T.; Walter, Nicholas D.; Robertson, Gregory T.; Slayden, Richard A. (Frontiers in Pharmacology, 2025)
IntroductionThe standard treatment for tuberculosis is the isoniazid, rifampicin, pyrazinamide, and ethambutol (HRZE) regimen. Despite its efficacy, this regimen has limitations, including prolonged treatment duration and poor clinical outcomes in drug-resistant cases. This back translational study assessed the efficacy of alternative drug combinations, focusing on high-dose rifamycins (rifampicin and rifapentine) and substituting moxifloxacin for ethambutol in the HRZE regimen. MethodsUsing a preclinical high-burden aerosol model of tuberculosis in BALB/c mice, we tested seven treatment combinations, including high-dose rifampicin (HD-RIF), high-dose rifapentine (HD-RPT), and moxifloxacin.ResultsBy day 12, the HD-RIF+HZM and HD-RPT+HZM regimens reduced lung bacterial burdens from 6.59 ± 0.08 log10 CFU in untreated controls to 3.70 ± 0.19 and 3.91 ± 0.43 log10 CFU, respectively. By day 54, bacterial loads were undetectable (<1 log10 CFU) in all groups except for HRZE (1.48 ± 0.32 log10 CFU). RS ratio analysis showed lower ratios for HD-RIF+HZM and HD-RPT+HZM compared to HRZE by day 26, indicating a superior ability of both regimens to interrupt rRNA synthesis. Histopathological analysis revealed similar granulomatous changes across all treatment groups. Mass spectrometry confirmed higher systemic exposure for HD-RIF and HD-RPT groups than RIF used in HRZE. DiscussionThe findings indicate that higher doses of rifamycins and the substitution of moxifloxacin offer improved bactericidal activity and could shorten TB treatment duration.